The Relationship between Environmental, Social, Governance, and Export Performance in Manufacturing Companies: A Literature Review - Li, Yan; Li, Jilian (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
The swiftness with which environmental, social, and governance (ESG) has progressed and taken root in the manufacturing industry has had an immense impact on performance. The impact of ESG on the environment in the manufacturing context, however, remains ambiguous. This investigation endeavors to present a review of the recent literature on the relationship between ESG and export performance, while simultaneously providing a roadmap for future inquiries. Employing content analysis techniques and the VOS viewer tool, this analysis scrutinizes salient research components such as journals, countries, regions, plausible links between ESG and corporate performance, and trends, with particular emphasis on the environmental pillar. Subsequently, a research agenda for ESG implementation is proposed that encompasses both conceptual and empirical perspectives, which includes: (i) identifying the optimum ESG level and its effects on export performance; (ii) exploring the inherent inverse causality within the ESG-export performance nexus; (iii) conducting international comparisons; and (iv) presenting various arguments that support an indirect link between ESG and export performance.